A hybrid DGTD-TDIE method for solving complex electromagnetic problems - Gao, S. P. (2013)
This paper presents a novel hybrid method that effectively combines two capable numerical methods – the discontinuous Galerkin time domain (DGTD) method and the time domain integral equation (TDIE) method. The hybrid DGTD-TDIE method is highly applicable to the interaction problem between arbitrarily shaped thin wires and dielectric structures with complex media compositions. The Huygens equivalence principle is employed to divide the original problem into two subproblems: (1) the region containing the thin wires, which is calculated by using the TDIE method, and (2) the dielectric region modeled by unstructured grids and analyzed by the DGTD method. A time-stepping scheme is used to match the different time steps between the DGTD and TDIE methods. To validate the hybrid method, several numerical results have been presented, which prove it a promising scheme to solve the complex coupling problems.